Analysis of Bone Density and Bone Morphometry by Periapical Radiographs in Dental Implant Osseointegration Process. (3rd April 2023) - Lubis, Ratih Trikusumadewi; Azhari, Azhari; Pramanik, Farina
Abstract : Objective . This research aimed to analyze the differences in bone density and bone morphometry by periapical implant radiography in the dental implant osseointegration stages. Methods . This experimental research uses 12 periapical radiographs of tibial bones from a New Zealand white rabbit ( Oryctolagus cuniculus ). The analysis was performed on day 3, 14, and 28 of the osseointegration stages with density, trabecular thickness (Tb.Th.), trabecular separation (Tb.Sp.), and trabecular number (Tb.N.) as parameters. The implant used is a titanium alloy and coated by SA (sunblasted with alumina acid) of 4 mm in diameter and 7 mm in length. The radiographic assessment of the osseointegration process is obtained with the region of interest (ROI) segmentation results. Additionally, each ROI was analyzed for bone density and morphometry using the open-source ImageJ software with the BoneJ plugin. The significant difference was evaluated by analysis of variance ( F -test) with p < 0.05 and nonparametric Kruskal–Wallis test with p < 0.05 . Results . Analysis of the osseointegration images of dental implants at day 3, 14, and 28 with the periapical X-ray modality shows significant differences (p < 0.05 ) in the parameters measuring density and trabecular thickness (Tb.Th.). In the variables of trabecular separation (Tb.Sp.) and number (Tb.N.) (p > 0.05 ), there is no significant difference. Conclusion . Based on the results, density and trabecular thickness (Tb.Th.) showed a significant difference between healing times. However, trabecular separation (Tb.Sp.) and trabecular number (Tb.N.) showed no difference in healing time.